1977
DOI: 10.1073/pnas.74.9.3956
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of an unstably inherited gene in cultured mouse cells.

Abstract: The specific activity of hypoxanthine-guanine phosphoribosyltransferase (IMP:pyrophosphate phosphoribosyltransferase, EC 2.4.2.8) is increased up to 58-fold in unstable gene transferents produced by the transfer of cell-free chromosomal material from one mouse L cell line to another; the specific activity of this enzyme returns to normal levels when the transferred gene becomes stabilized. This phenomenon, which is not observed 'in comparable heterospecific transfers, may be an effect of gene dosage (multiple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

1979
1979
1998
1998

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 10 publications
2
12
0
Order By: Relevance
“…Two-dimensional gel electrophoresis analysis of unstable CMGT cell lines demonstrated that HPRT polypeptides were overexpressed, corroborating previous findings of increased HPRT enzyme activity in these cells (5). Dot blot hybridization experiments showed that HPRT mRNA levels were elevated 10-to 15-fold in the GT427C line.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Two-dimensional gel electrophoresis analysis of unstable CMGT cell lines demonstrated that HPRT polypeptides were overexpressed, corroborating previous findings of increased HPRT enzyme activity in these cells (5). Dot blot hybridization experiments showed that HPRT mRNA levels were elevated 10-to 15-fold in the GT427C line.…”
Section: Discussionsupporting
confidence: 73%
“…In the present study, we were unable to detect increased levels of expression of any other polypeptides in addition to HPRT by two-dimensional gel electrophoresis analysis. Previous experiments have shown that the levels of expression of the linked glucose-6-phosphate dehydrogenase gene were normal in GT427C and GT427D (5 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, the initial drug resistance was obtained by DNA-mediated gene transfer. Observations of initial instability of such resistance (33,49,61), suggestions of amplification of the transferred genes during this period (18,50), probable extrachromosomal maintenance of the transferred DNA during the unstable phase (33,44), and evidence for stabilization of the resistance by chromosomal integration of the transferred DNA (33,47,49) mirror the results obtained when cell mutants are selected in vitro for increasing drug resistance (1, 8, 14, 30, 41, 51, 58, 60). By applying an initial mild selection pressure after exposure to DNA, followed quickly by stepwise increases in the selection stringency ( (42).…”
Section: Discussionmentioning
confidence: 49%
“…On my return to Yale, Jody and I carried out a number of experiments on the cell fusion process (59) and I collaborated with Irv Miller, Jerry Eisenstadt, and Jerry Degnen on gene transfer between lines of cultured mammalian cells (22,23). While this work was going on, I was following with interest a small but growing literature on membrane transport systems in established lines of cultured mammalian cells.…”
Section: Membrane Transport In Mammalian Cellsmentioning
confidence: 99%